Interstellar scintillation as a cosmological probe: Prospects and challenges - Koay, J.; Macquart, Jean-Pierre; Rickett, B.; Bignall, Hayley; Jauncey, D.; Lovell, J.; Reynolds, C.; Pursimo, T.; Kedziora-Chudczer, L.; Ojha, R (Cambridge University Press, 2012)
The discovery that interstellar scintillation (ISS) is suppressed for compact radiosources at z 2 has enabled ISS surveys to be used as cosmological probes. We discuss brieflythe potential and challenges involved in such an undertaking, based on a dual-frequency surveyof ISS carried out to determine the origin of this redshift dependence.